The Role of Regional Honor Council in Maintaining the Honor of Notary Position - Isro Vita Nugrahaningsih (Jurnal Ilmu Kenotariatan, 2023)
A profession that in carrying out its duties, functions and authorities requires an ethics, so does a Notary. So the code of ethics is used as a guideline for the behavior of members of the profession in acting and behaving. The existence of a Notary code of ethics aims to make the Notary profession run professionally with motivation and orientation to intellectual skills as well as rational and critical argumentation as well as upholding moral values. So that the notary in carrying out his position is supervised by the Notary Honorary Council, because this supervisory function is very necessary so that the Notary does not ignore the nobility and dignity of his profession. Writing this article aims to identify, examine and analyze the role of the Honorary Board in maintaining the honor of the position of Notary Public by upholding a code of ethics. This writing uses a normative juridical approach, using primary and secondary legal sources. Primary legal materials are obtained from laws and regulations and secondary legal materials are obtained from library materials, archives, and documents related to the object of research. The results of the discussion show that the position of the Honorary Board in the Notary organization has a strategic and important role in enforcing the code of ethics as an effort to maintain the honor of a notary. The Honorary Council in enforcing the Notary's code of ethics identifies, evaluates and improves the supervisory system for Notaries so that violations of the code of ethics can be minimized, the Honorary Council makes strategic steps to be implemented and used according to the objectives to be achieved. KEYWORDS : Code of Ethics, Honor Council, Notary.